2021 Thai Aneurysmal Subarachnoid Hemorrhage Practice Guidelines - สกุลณะมรรคา, สิรรุจน์; ศิวานุวัฒน์, รุ่งศักดิ์; ประเสริฐ, ยอดรัก; วีรสาร, กุลพัฒน์; รักษ์กุล, ภัทรวิทย์; ตันทองทิพย์, ดิลก; ดวงทองพล, พิชเยนทร์; แซ่เฮ้ง, ศักดิ์ชัย; วงศ์สุริยนันท์, สมเกียรติ; ธัญยนพพร, จักรี; นาคลออ, พีระ; เทียนศรี, ธนกร; et al. (Thai Journal of Neurological Surgery, 2025)